Index of verb forms in Thucydides - Stork, Peter. (Classical Studies E-Books Online, Collection 2008, ISBN: 9789004222793., 2008)
This index lists all verb forms in Thucydides, with the total number of occurrences of the verbs and crossreferences to the compounds. Two appendices provide lists of verb forms that are attested in the manuscripts but have been removed by conjecture from the printed text and of all attested variant readings. In providing easy access to the verb system as it is attested in Thucydides, it is an invaluable tool for research into the verb system in Thucydides in particular and in Ancient Greek in general, on matters of lexicography or morphology, and more particularly on various aspects of the semantics of the verb system, such as the use of aspectual forms and that of the moods and voices.